Educação do campo e agroecologia nas práticas agroecológicas em escolas do campo: as vivências nos territórios das escolas Iraci Salete Strozak (PR) e Maria Nazaré de Sousa (CE) - Barbosa, Francisco Flavio Pereira (2018)
The present dissertation Education in the Countryside and Agroecology: Production of Knowledge in the Schools Maria Nazaré de Sousa and Iraci Salete Strozak, is an effort to synthesize a militant experience, a collective experience shared in the MST in Ceará state and in the momentum in which Education in the Countryside and Agroecology, acquire a significant dimension in the scope of the academic formation at the Federal University of the South Frontier - UFFS.The approach in this research was based on documents of the MST‟s Education Sector, in its work in Rural Elementary Schools, in the states of Ceará and Paraná, with the intention of developing an intersectorial and interdisciplinary action in the Education, Production and Youth sectors. The research took place in two schools - Iraci Salete Strozak (PR) and Maria Nazare de Sousa -, through participatory observation, analysis of school documents and observation of an Education in the Countryside project, based on the Agroecological production, and in the humanization of the work through the teachinglearning process of peasant youth, in the schools and in the daily life of their communities.The purpose of this dissertation is to map and analyze the experiences of agroecology in the investigated schools, emphasizing the production of agroecological knowledge, gatherings, experiences and actions developed in both spaces.The dissertation is structured in the following contents: elements for the design of an education proposal in the MST and a socialist pedagogy; the experience of an educational practice in agroecology and the educational dimension of Food Sovereignty; the interdisciplinary assumptions of agroecology, and the mechanisms of peasant resistance and self-determination; environmental studies and the critique of the ideology of progress to understand Agroecology, the most practices types of sustainable agriculture, the principles of ecological agriculture in its dimension of challenge chemical agriculture, highlighting the pertinent question on Agroecology as a science or interdisciplinary field.We also bring the elements of the People‟s Agrarian Reform and the debate on Food Sovereignty, contextualizing the agroecological perspective in the MST, and observing the challenges and limits of agroecology in Brazil. We approach education and agroecology in the experience of the Iraci Salete Strozak and Maria Nazaré de Sousa Schools, highlighting their historical antecedents, the organicity of the pedagogy of the Movement and struggle, shaping their Political and Pedagogical Projects. In the analysis we highlight the educational times and the cycles of human formation in the curricula development and in an effort of synthesis, this Dissertation tries to capture - from the direct observation and the analyzed documents - the knowledge in agroecology in the experience of the two schools, as social places and conquered territories.